Efeitos de sistemas de preparo do solo sobre o consórcio milho-feijão (Phaseolus vulgaris L.) - Vieira Sampaio, Giderval; Domingos Galvão, José; Nogueira Fontes, Luiz Antônio; de Souza Figueiredo, Matosinho; Cardoso, Antônio Américo (Revista Ceres, 2025)
The effect of different plowing systems on the characteristics and productici: of intercropped maize and beans, grown during the wet and dry seasons, was evaluated. Treatments consisted of no tillage, molboard plowing, disk plowing, and heavy disk harrowing + moldboard plowing, heavy disk harrowing + disk plowing, heavy disk harrowing. The soil was a red-yellow cambic Podzol.